Political Participation and Social Environment - Imbrasaitė, Jūratė (Sociologija. Mintis ir veiksmas, 2002)
Modern democratic policy is essentially grounded on participation of citizens in public decision-making process. The focus of the study was the impact of social environment on political participation. The method of study was survey sample data analysis. The results of analysis reflect relationship between number of people whom respondent discuss about political and societal matters and political participation. Data anlysis confirm an assumption that social environment has impact on political behaviour, i.e. in some cases social environment could encourage low status group political participation or discourage high status group political participation.